Emotion as a source of moral understanding in conservation. Issue 5 (8th March 2021) - Batavia, Chelsea; Nelson, Michael Paul; Bruskotter, Jeremy T.; Jones, Megan S.; Yanco, Esty; Ramp, Daniel; Bekoff, Marc; Wallach, Arian D.
Abstract: Recent debates around the meaning and implications of compassionate conservation suggest that some conservationists consider emotion a false and misleading basis for moral judgment and decision making. We trace these beliefs to a long‐standing, gendered sociocultural convention and argue that the disparagement of emotion as a source of moral understanding is both empirically and morally problematic. According to the current scientific and philosophical understanding, reason and emotion are better understood as partners, rather than opposites. Nonetheless, the two have historically been seen as separate, with reason elevated in association with masculinity and emotion (especially nurturing emotion) dismissed or delegitimated in association with femininity. These associations can be situated in a broader, dualistic, and hierarchical logic used to maintain power for a dominant male (White, able‐bodied, upper class, heterosexual) human class. We argue that emotion should be affirmed by conservationists for the novel and essential insights it contributes to conservation ethics. We consider the specific example of compassion and characterize it as an emotional experience of interdependence and shared vulnerability. This experience highlights conservationists' responsibilities to individual beings, enhancing established and widely accepted beliefs that conservationists have a duty to protect populations, species, and ecosystems (or biodiversity). We argue compassion, thus understood, should be embraced as a core virtue of conservation. Abstract : Article impact statement : Conservationists should accept that emotions like compassion provide insights that can help them understand and navigate their moral lives. Abstract : El Sentimiento como Fuente de Entendimiento Moral en la Conservación Resumen: Los debates recientes en torno al significado y las implicaciones de la conservación compasiva sugieren que algunos conservacionistas consideran al sentimiento como una base falsa y engañosa para el juicio moral y la toma de decisiones. Seguimos estas creencias hasta una convención sociocultural prolongada y relacionada con el género y argumentamos que el menosprecio por el sentimiento como fuente del entendimiento moral es problemático empírica y moralmente. De acuerdo con el conocimiento científico y filosófico actual, la razón y el sentimiento se entienden de mejor manera como pareja, en lugar de como opuestos. Sin embargo, ambos conceptos han estado históricamente separados, con la razón como concepto elevado asociado con la masculinidad y el sentimiento (especialmente el sentimiento de crianza) rechazado o deslegitimado en asociación con la feminidad. Estas asociaciones pueden situarse dentro de una lógica más general, dualista y jerárquica usada para mantener el poder de la clase humana del macho dominante (blanco, sin discapacidades, de clase alta, heterosexual). Sostenemos que el sentimiento debería ser ratificado por los conservacionistas por el conocimiento novedoso y esencial que contribuye a la ética de la conservación. Consideramos el ejemplo específico de la compasión y lo caracterizamos como una experiencia emocional de la interdependencia y la vulnerabilidad compartida. Esta experiencia resalta las responsabilidades que los conservacionistas tienen con los individuos, fortaleciendo las creencias establecidas y ampliamente aceptadas de que los conservacionistas tienen el deber de proteger a las poblaciones, especies y ecosistemas (o a la biodiversidad). Sostenemos que la compasión, entendida así, debería ser aceptada como una virtud nuclear de la conservación.